2017
DOI: 10.1590/1809-2950/15886624012017
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-rater reliability of computerized photogrammetry and universal goniometer in the measurement of hip flexion and abduction

Abstract: The universal goniometer (UG) is the most frequently used tool for measuring range of motion (ROM), with demonstrated reliability. Computerized photogrammetry (CP) is widely used for postural assessment, but its role in the measurement of ROM of hip flexion and abduction has not yet been fully explored. This study aimed to test inter- and intra-rater reliability for measuring ROM of hip flexion and abduction using UG and CP, as well as the reliability between the instruments. Our sample consisted of 40 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although the UG is considered a gold standard in evaluations of joint range of motion, it presents significant differences for hip flexion (113°-141°). 10,[16][17][18][19] New measurement instruments such as accelerometers, which do not rely on external references, would enable hip assessments with pelvic monitoring in a simple way. This study measured pelvis retroversion during hip flexion evaluations by accelerometers and obtained an average result near to 7.3º, in the sample evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the UG is considered a gold standard in evaluations of joint range of motion, it presents significant differences for hip flexion (113°-141°). 10,[16][17][18][19] New measurement instruments such as accelerometers, which do not rely on external references, would enable hip assessments with pelvic monitoring in a simple way. This study measured pelvis retroversion during hip flexion evaluations by accelerometers and obtained an average result near to 7.3º, in the sample evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the alignment of the arms is visual and subjective. 13,14 New tools have been used in the assessment of joint range of motion to make the process simpler and more accurate, such as: inclinometers 15,16 , smartphone apps 17 , photogrammetry 18 , image tests 19 and the Inertial Movement Unit (IMU). 20 Recent studies on the assessment of human gait have shown that IMU -motion sensor typically composed of acceleration transducers (accelerometers), rotation (gyroscopes) and magnetic orientation (magnetometers) -, present accurate results in kinematic knee and hip evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…The big toe was kept pointing towards the sky to prevent rotation of the femur during hip abduction. 17 When measuring ROM, the axis of the goniometer was placed in the ASIS and the stationary and movable arms were placed at the anterior midline of the femur (patellar midline).…”
Section: Journal Of Musculoskeletal Science and Technologymentioning
confidence: 99%
“…Goniometry plays an essential role in the clinical measurement of range of motion (Gajdosik and Bohannon 1987;Pazira et al 2016). It is apparent from several papers that traditional plastic goniometer evaluates hip and knee joint angles efficiently and reliably; however, use of goniometer requires careful attention in evaluation (Kim 2018;Marques et al 2017;Charbonnier et al 2015;Gajdosik and Bohannon 1987;Rheault et al 1988).…”
Section: Outcome Parametersmentioning
confidence: 99%